1999
DOI: 10.1523/jneurosci.19-24-10948.1999
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Cell Tropism, Replication, and Gene Transfer in Brain

Abstract: Cytomegalovirus (CMV) infects a majority of adult humans. During early development and in the immunocompromised adult, CMV causes neurological deficits. We used recombinant murine cytomegalovirus (mCMV) expressing either green fluorescent protein (GFP) or ␤-galactosidase under control of human elongation factor 1 promoter or CMV immediate early-1 promoter as reporter genes for infected brain cells. In vivo and in vitro studies revealed that neurons and glial cells supported strong reporter gene expression afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
116
1
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 125 publications
(128 citation statements)
references
References 61 publications
(46 reference statements)
8
116
1
3
Order By: Relevance
“…The adult brain is protected from CMV by a number of mechanisms, including a CD4 (39) and peripheral CD8 (36) T-cell response. We have previously shown that developing brain cells in vivo and in vitro are more likely to show mCMV infections than mature brain cells, and that this preference is independent of the host B-and T-cell responses (57,61). In the present study, we compared the innate IFN-mediated antiviral responses to mCMV in mature and developing brains.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The adult brain is protected from CMV by a number of mechanisms, including a CD4 (39) and peripheral CD8 (36) T-cell response. We have previously shown that developing brain cells in vivo and in vitro are more likely to show mCMV infections than mature brain cells, and that this preference is independent of the host B-and T-cell responses (57,61). In the present study, we compared the innate IFN-mediated antiviral responses to mCMV in mature and developing brains.…”
Section: Discussionmentioning
confidence: 84%
“…We next tested the hypothesis that human brain cells are similarly protected from hCMV by IFN and that hCMV infection induces an antiviral response from human brain cells. Primary human brain cells were cultured and then infected with an hCMV that contains a gene coding for GFP (25,57). Two types of human brain cells were used.…”
Section: Induction Of Intrinsic Antiviral Response By Neurons and Glimentioning
confidence: 99%
“…However, the temporal course of these changes was different, which could be attributed to HCMV doses. Syncytia formation has also been reported in other cellular types, and it seems to be related to cell fusion induced by viral glycoproteins present in the plasma membrane (Belec et al 1990;van Den Pol et al 1999;Kinzler and Compton 2005). On the other hand, when we infected SK-N-MC with the MOI of 0.01, cellular prolongations were observed suggesting cellular differentiation to a neuron-like morphology, an unexpected finding since we did not add any other stimulus that may account for these changes, and this normally does not occur in an spontaneous way (Higgins et al 2009).…”
Section: Discussionmentioning
confidence: 91%
“…28,56 These findings argue against direct virus cytopathology and suggest an indirect, virus-induced mechanism as more probable. CNS structural abnormalities and functional disorders caused by congenital CMV infection may be due to MCMV infection of radial glial cells, which play an important role in guiding neuron migration in the neonatal mouse cerebrum, [58][59][60] but could also be the result of an insufficient cerebral blood supply caused by endothelial cell infection and inflammation of the vessel wall 61 (Figure 1b) or by infection of NSPCs. 47,54,62 NSPCs, which are located predominantly in the ventricular/periventricular zone, have the ability to migrate, proliferate, and differentiate into neurons, astrocytes, and oligodendrocytes and are fully permissive to CMV infection.…”
Section: Cmv-induced Developmental Brain Abnormalitiesmentioning
confidence: 99%